2015
DOI: 10.1074/jbc.m115.636746
|View full text |Cite
|
Sign up to set email alerts
|

An N-terminal Amphipathic Helix Binds Phosphoinositides and Enhances Kalirin Sec14 Domain-mediated Membrane Interactions

Abstract: Background: Promoter usage determines the peptide preceding the lipid-binding KalSec14 domain.Results: Kalirin C-promoter encodes an amphipathic helix, which interacts with phosphoinositides, localizes to the trans-Golgi network, alters KalSec14 interactions with cell membranes, and stimulates secretion. Conclusion: Sec14 domain function is altered by the preceding phosphoinositide-binding amphipathic helix. Significance: Kalirin function is expected to vary with promoter choice.Previous studies revealed an es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 63 publications
0
37
0
Order By: Relevance
“…We found that residues 190–202 formed an amphipathic helix with an array of hydrophobic residues located on one side. This observation is reminiscent of the protein/membrane interaction through amphipathic helices in the cases of KalSec14, Atg3, PB1-F2 etc 20212223. In this model an amphipathic helix can immerse its hydrophobic side into the lipid bilayer through hydrophobic interactions.…”
Section: Discussionmentioning
confidence: 93%
“…We found that residues 190–202 formed an amphipathic helix with an array of hydrophobic residues located on one side. This observation is reminiscent of the protein/membrane interaction through amphipathic helices in the cases of KalSec14, Atg3, PB1-F2 etc 20212223. In this model an amphipathic helix can immerse its hydrophobic side into the lipid bilayer through hydrophobic interactions.…”
Section: Discussionmentioning
confidence: 93%
“…While Kal7 is largely particulate, much of the Kal9/Kal12 is soluble 11, 22 . Since a difference in subcellular localization could result in exposure to different protein kinases, we asked whether the extent of phosphorylation at sites common to Kal7, Kal9 and Kal12 differed.…”
Section: Resultsmentioning
confidence: 99%
“…Immunoprecipitation was carried out with slight modifications of the protocol described previously 36 using affinity-purified antibody to the Sec14 domain of Kalirin 22 For each sample, 0.8 volumes of 10% NP-40 (Pierce, SurfActs) treated with orthovanadate and PhosSTOP was added to an aliquot containing 2 mg protein; samples were allowed to rotate end over end in the cold room for 20 min and then centrifuged at 4C for 15 min at 14,000 × g to remove any insoluble material. Supernatants were then further diluted with 3.5 volumes TM-P (20 mM Na TES, 10 mM mannitol, 5 mM EDTA, 50 mM NaF, 10 mM Na pyrophosphate, pH 7.4) containing 1 mM orthovanadate, 1 tablet PhosSTOP/10 ml and Calbiochem Phosphatase Inhibitor Cocktail I.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As levels of PHn-CC-EX rose, levels of Kal7 and Tiam1 C1199 proteins fell. Kal7 and Tiam1 share the ability to interact with phosphoinositides and with EphB2, NMDA receptors and spinophilin (Kiraly et al, 2011; Miller et al, 2015; Terawaki et al, 2010). The ability of PHn-CC-EX to bind phosphoinositides and multiple proteins (Joshi et al, 2013; Stam et al, 1997; Terawaki et al, 2010) may account for its ability to disrupt Rac1 activation by Kalirin.…”
Section: Resultsmentioning
confidence: 99%